Processual models of radicalization into terrorism : a best fit framework synthesis - De Coensel, Stéphanie (Journal for deradicalization, 2018)
The pre-emptive turn in the criminal justice system, and more in particular in the counterterrorism context, has brought legislators to intervene as early as possible and to target remote risks. However, when drafting far-reaching legislation, hardly any attention is given to the underlying phenomena. This article therefore aims to review existing processual models of radicalization that provide insight into the sequence of the trajectory towards terrorism. These models are often isolated and comparative reviews have been scarce and partial in scope. Through a best fit framework synthesis, this contribution systematically identifies existing models and frameworks in the literature and analyses them thematically. As a result, a meta-framework, represented by an eight-phased horizontal funnel, embodies the current state of research on phase models of radicalization. The eight phases cover the entire process from pre-radicalization, to five radicalization phases sensu stricto, to implementation and post-implementation. In these phases, multiple concepts that relate to grievances, cognitions, groups and violence are identified. The meta-framework, or integrated funnel model, evidences the pre-crime hypothesis and shows that far-reaching criminal law provisions intervene at too early stages of the radicalization process